The Association between Type-2 Diabetes Duration and Major Adverse Cardiac Events after Percutaneous Coronary Intervention - Botey Katamu Benjamin; Chunguang Qiu; Zhanying Han; Wenjie Lu; Guoju Sun; Xiaofei Qin; Xule Wang; Xi Wang; Ran Li; Liang Pan (Journal of Diabetes Research)
Background. Diabetes is an independent risk factor for coronary artery disease and portends adverse prognosis in diabetic patients undergoing percutaneous coronary intervention (PCI) compared to nondiabetic patients. Few studies are currently available regarding the relationship between diabetes duration and major adverse cardiac events (MACEs) post-PCI. This study is aimed at assessing the association between diabetes duration and major adverse cardiac events after PCI. Methods. A total of 302 cases of diabetic patients undergoing an elective PCI with drug-eluting stent (DES) deployment and or percutaneous transluminal coronary angioplasty (PTCA) using a drug-coated balloon (DCB) were prospectively studied. We divided patients into three groups based on diabetes duration: <5 years group (n=165), 5–10 years’ group (n=72), and ≥10 years’ group (n=65). Angiographic and clinical follow-up were conducted 12 months after the procedures for all the patients and at any given time during the study when needed. Results. A significantly higher rate of myocardial infarction (MI) in diabetic patients with the longest diabetes duration (7.7% vs. 0% and 0.6%, P=0.001) was observed compared with groups of shorter duration. Repeat coronary revascularization was found to be significantly higher in the >10-year group than was it in groups with shorter duration of diabetes (23.1% vs. 19.4% and 9.10%, P=0.03). After adjustment for confounding risk factors, longer diabetes duration remained an independent predictor of MI (hazard ratio (HR): 5.525, confidence interval (CI): 1.273-23.978, P=0.022) and repeat revascularization (HR: 1.608, CI: 1.058-2.443, P=0.026). Repeat revascularization was significantly related to the progression of nontreated lesions (De novo lesions 20% vs. 18% and 7.3%, P=0.009) compared to previously treated lesions (target lesion revascularization (TLR) 3% vs. 1.3% and 2%, P=0.774). However, all-cause mortality was not significantly different among the groups (3.1% vs. 5.6% and 0.6%, P=0.06, HR: 2.403, CI: 0.464-12.436, P=0.293). Conclusion. Diabetes duration was associated with significant differences in major adverse cardiac events after the percutaneous coronary intervention; the longest diabetes duration portended higher rates of MACEs than shorter duration at the 12-month follow-up.